ANALISIS KERENTANAN PANTAI MARON DAN PANTAI TIRANG KECAMATAN TUGU, KOTA SEMARANG (Analysis of Coastal Vulnerability on the Maron Beach and Tirang Beach at Tugu Subdistrict, Semarang City) - Prabowo, Danar; Muskananfola, Max Rudolf; Purwanti, Frida (Management of Aquatic Resources Journal (MAQUARES), 2017)
Pantai Maron dan Pantai Tirang merupakan daerah wisata di wilayah pesisir Semarang. Nilai kerentanan pantai tersebut perlu diketahui agar pemanfaatannya tidak terganggu. Pantai Maron dan Pantai Tirang Kecamatan Tugu, Kota Semarang, dianalisis menggunakan metode CVI (Coastal Vulnerability Index), dilakukan pada bulan Mei sampai dengan Juni 2017. Tujuan penelitian ini adalah mengidentifikasi kondisi kerentanan Pantai Maron dan Pantai Tirang, dan mengetahui nilai indeks kerentanan ekosistem Pantai Maron dan Pantai Tirang, Kecamatan Tugu, Kota Semarang. Metode CVI (Coastal Vulnerabilty Index), dilakukan dengan cara menilai kerentanan pantai pada variabel kemiringan pantai, jarak tumbuhan dari pantai, pasang surut rata-rata, tinggi gelombang rata-rata, dan erosi/akresi pantai berdasarkan tabel indeks kerentanan pantai pada lima sel pantai. Hasil penelitian menunjukkan bahwa nilai CVI Pantai Maron antara 6,45 – 9,13 termasuk dalam kategori kerentanan pantai yang rendah (>20,5), sedangkan nilai CVI Pantai Tirang yaitu 10,21 dan 22,82 termasuk dalam kategori kerentanan rendah dan menengah (20,5 – 25,5). Kesimpulan yang dapat disampaikan adalah nilai kerentanan Pantai Maron dan Pantai Tirang, Kecamatan Tugu, Kota Semarang berdasarkan variabel fisik termasuk dalam kategori rendah dan menengah. Maron and Tirang beaches are tourism area in the coastal area of Semarang. The value of vulnerability of the coast should be known so its utilization will not be disturbed. The Maron Beach and Tirang Beach used Coastal Vulnerability Index method. The research was carried out from Mei to June, 2017. The aims of this study are to identify vurnerability conditions of Maron Beach and Tirang Beach, and to know vulnerability index value of Maron Beach and Tirang Beach, Tugu Subdistrict, Semarang City. CVI method used by scoring coastal vulnerability on variables of coastline slope, plants distance from the coast, average tidal range, average wave height, and coastline changes (accresion/erosion) based on table of coastal vulnerability index at five coastal cells. The research show that the CVI value of the Maron Beach 6,45 into 9,13 that include in the low coastal vulnerability category (<20,5), while CVI value of the Tirang Beach 10,21 and 22,82 that include in the low and middle coastal vulnerability category (20,5-25,5). Conclusion of this research is coastal vulnerability index of Maron Beach and Tirang Beach, Tugu Subdistrict, Semarang City based on physical variables belong to low and middle vulnerability.   GMT Detect languageAfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBasqueBelarusianBengaliBosnianBulgarianCatalanCebuanoChichewaChinese (Simplified)Chinese (Traditional)CorsicanCroatianCzechDanishDutchEnglishEsperantoEstonianFilipinoFinnishFrenchFrisianGalicianGeorgianGermanGreekGujaratiHaitian CreoleHausaHawaiianHebrewHindiHmongHungarianIcelandicIgboIndonesianIrishItalianJapaneseJavaneseKannadaKazakhKhmerKoreanKurdishKyrgyzLaoLatinLatvianLithuanianLuxembourgishMacedonianMalagasyMalayMalayalamMalteseMaoriMarathiMongolianMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanScots GaelicSerbianSesothoShonaSindhiSinhalaSlovakSlovenianSomaliSpanishSundaneseSwahiliSwedishTajikTamilTeluguThaiTurkishUkrainianUrduUzbekVietnameseWelshXhosaYiddishYorubaZulu AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBasqueBelarusianBengaliBosnianBulgarianCatalanCebuanoChichewaChinese (Simplified)Chinese (Traditional)CorsicanCroatianCzechDanishDutchEnglishEsperantoEstonianFilipinoFinnishFrenchFrisianGalicianGeorgianGermanGreekGujaratiHaitian CreoleHausaHawaiianHebrewHindiHmongHungarianIcelandicIgboIndonesianIrishItalianJapaneseJavaneseKannadaKazakhKhmerKoreanKurdishKyrgyzLaoLatinLatvianLithuanianLuxembourgishMacedonianMalagasyMalayMalayalamMalteseMaoriMarathiMongolianMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanScots GaelicSerbianSesothoShonaSindhiSinhalaSlovakSlovenianSomaliSpanishSundaneseSwahiliSwedishTajikTamilTeluguThaiTurkishUkrainianUrduUzbekVietnameseWelshXhosaYiddishYorubaZulu         Text-to-speech function is limited to 200 characters  Options : History : Feedback : DonateClose